Entrepreneurial Behaviour and their Correlates among Dairy Entrepreneurs in Northern India - Shah, Ajay Kumar; Nishi,; Malik, B.S.; Yadav, V.K. (Indian Journal of Extension Education, 2010)
A study was conducted in Northern states (Haryana and Uttar Pradesh) of India to assess the entrepreneurial behaviour of dairy entrepreneurs. Karnal and Lucknow districts were selected randomly from Haryana and Uttar Pradesh, respectively. Two blocks from each selected district was selected randomly. Within each selected block a cluster of villages was formed and from each cluster of villages 45 entrepreneurs were selected on proportionate random sampling basis, thus a total 180 respondents were selected. The data were collected by conducting personal interview of respondents with the help of modified interview schedule. Entrepreneurial behaviour of respondents was measured by executing entrepreneurial Self Assessment Scale. The association of independent variables viz., socio-economic, communication and psychological variables with entrepreneurial behaviour of farmers was assessed and contributory influence of these independent variable on dependent variable i.e. Entrepreneurial Behaviour was also estimated. The results revealed that large majority of dairy entrepreneurs are moderate in their entrepreneurial ability. The individuals rich in entrepreneurial attributes can be role models for isolated group of diary farmers who are still to venture out in dairy entrepreneurship. As a result of relational analysis, it was found that herd size, milk yield, total income, mass media exposure, knowledge and economic motivation of the respondents had positive and significant contribution on the entrepreneurial behaviour. Family size negatively and significantly contributed towards entrepreneurial behaviour. However, age and milk sale were not contributing towards possession of entrepreneurial characteristics by the dairy entrepreneurs.